(Nano)Fibrillar morphology development in biobased poly(butylene succinate‐co‐adipate)/poly(amide‐11) blown films. Issue 5 (21st January 2021) - Dadouche, Tarek; Yousfi, Mohamed; Samuel, Cédric; Lacrampe, Marie‐France; Soulestin, Jérémie
Abstract: Thin films with (nano)fibrillar morphologies were successfully obtained in fully‐biobased poly(butylene succinate‐co‐adipate)/poly(amide‐11) blends (PBSA/PA11, 85/15 wt/wt) using an extrusion‐blowing process. Impacts of PA11 grade and take‐up ratio on the morphology of PBSA/PA11 were particularly highlighted. Scanning electron microscopy analyses indicated that PA11 with high melt volume‐flow rates are beneficial to the development of (nano)fibrillar morphologies in PBSA/PA11 blown film. On the contrary, unstable film blowing processing without fibrillar morphologies was attested for PA11 with low melt volume‐flow rates. Increasing the take‐up ratio during extrusion‐blowing of PBSA/PA11 clearly generates finer PA11 (nano)fibrils into PBSA. Fibril diameters down to 300 nm could be reached with an optimal PA11 grade promoting enhanced mechanical properties (higher ductility and toughness). The formation of stable PA11 (nano)fibrils into PBSA is discussed via rheological assessments of viscosity/elasticity ratio. A specific attention was finally paid to the PBSA strain‐hardening behavior in PBSA/PA11 using elongational rheological tests. PA11 (nano)fibrillation helps maintaining the strong PBSA strain‐hardening and thus play a major role on the processability of PBSA/PA11 blends by extrusion blowing. As a conclusion, the PA11 grade represents a crucial parameter to control the production of PBSA/PA11 blown films with refined (nano)fibrillar structures and enhanced physico‐chemical properties. Abstract :